Gender Inequality is not a "Women Only" Issue: A Case Study of Egyptian Private News Media - Ahmed, Amira (AUC Knowledge Fountain, 2024)
Discrimination in the workplace among different genders is a significant issue in the news media sector globally. This study aims to determine and measure gender inequality in the Egyptian private news media sector through different indicators, including job payments, workload, promotions, media roles, work safety, and work flexibility, especially post-COVID. A mixed approach was used by conducting sixteen interviews and then a survey of 304 private news media sector participants. As inequalities can be a double-faced case, men's and women's perspectives have been considered in the study sample. Through descriptive and statistical analysis, the research findings revealed new insights to formulate new workplace policies that protect female and male private news media employees' rights. Parental leave and flexible work policies are the top priorities to achieve gender equality. Female journalists were more likely to feel that they were treated unequally. Also, there were highly significant statistical differences indicating that male journalists reported greater workload compared to female journalists (p< 0.001). Thus, gender issues need to be further studied post-Covid new work arrangements. In order to advance gender equality, comprehensive legislation that provides men with sufficient paid parental leave and women with fair promotions is essential, and cultural beliefs should be changed.